Effect of Service Performance on Consumer Loyalty in North Cyprus Hotel Sector - Şenyiğit, Doğa (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
In the context of major contributions into tourism development, four- and five-star hotels play vital role in the economy of Northern Cyprus. Based on previous studies related to service performance, RESERVE scale developed and proposed to the readers. The main objective of this study is to find out what are the effects of service performance on the loyalty of the consumers in North Cyprus hotel industry. This research also attempts to find out the mediating role of the consumer satisfaction between the consumer loyalty and service performance. The data was collected using self-administrated survey from 240 hotel guests who have stayed in four- and five-star hotels in Northern Cyprus. The findings revealed that there is significant positive correlation between the consumer loyalty and service performance. Although, the main results also demonstrated that consumer satisfaction does not act as a mediator between the consumer loyalty and service performance. Also, managerial and theoretical implications become available on the basis of the study findings in the thesis. In addition, information related to limitations and recommendations of the study for future research is shown in the last chapter of the thesis.

ÖZ: Turizmin gelişimine katkılarından dolayı, dört ve beş yıldızlı oteller, Kuzey Kıbrıs ekonomisinde önemli bir rol oynarlar. Daha önce yapılan çalışmalara dayanarak RESERVE ölçeği geliştirilip, okuyuculara sunulmuştur. Bu araştırmanın amacı, Kuzey Kıbrıs’taki otel endüstrisinde, hizmet performansının müşteri sadakatındaki etkisini ölçmektir. Bu çalışmada ayrıca müşteri memnuniyetinin, hizmet performansı ile müşteri sadakati arasındaki arabulucu rolü incelenmiştir. Kuzey Kıbrıs’taki dört ve beş yıldızlı otellerde kalan 240 otel müşterisinden anket yolu ile veriler toplanmıştır. Sonuçlar hizmet performansı ve müşteri sadakati arasındaki ilişkinin olumlu yönde olduğunu göstermiştir. Ancak, aynı sonuçlar müşteri memnuniyetinin, hizmet performansı ile müşteri sadakati arasında arabulucu rolünün etkin olmadığını göstermektedir. Ayrıca, tezdeki bulgular doğrultusunda araştırma ve yönetsel belirlemelere yer verilmiştir. Buna ilaveten, araştırmanın sınırları ile gelecek araştırmalar için öneriler de tezin son ünitesinde sunulmuştur.
Master of Science in Tourism Management. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Tourism, 2019. Supervisor: Prof. Dr. Hasan Kılıç
Keywords: Tourism Faculty; Customer Satisfaction--Tourism--Cyprus, North; Hospitality Industry--Management--Service Quality--Tourism--Hotel Sector; Consumer Behaviors--Loyalty--Hotel Sector--Cyprus, North; Hotel industry, Consumer satisfaction, Consumer loyalty, Service performance, Northern Cyprus